HUBUNGAN KONDISI GEOLOGI TERHADAP SEBARAN KADAR CU-AU BERDASARKAN DATA INTI PENGEBORAN PROSPEK TUMPANGPITU, DAERAH SUMBERAGUNG, BANYUWANGI, JAWA TIMUR: RELATIONSHIP BETWEEN GEOLOGICAL CONDITIONS AND Cu-Au GRADE DISTRIBUTION BASED ON DRILL CORE DATA FROM TUMPANGPITU PROSPECT, SUMBERAGUNG AREA, BANYUWANGI, EAST JAVA - Riyanto, Putri Rindu Bunga Kasih; Dadan Wildan; Achmad Djumarma Wirakusumah; Tatik Handayani; Riansyah Widisaputra (Buletin Sumber Daya Geologi, 2025)
The research area is located in Pesanggaran, Banyuwangi, East Java, situated in the central part of the Sunda-Banda magmatic arc, with potential for mineralization. The research aims to identify geological conditions, alteration zones, mineralization, ore deposit types, and their relationship with the distribution of Cu-Au grades. The results of the study can be used as a reference for further exploration. The research is based on core drilling data from six locations, ASD analysis, X-RD, petrography, ore microscopy, and statistical analysis using boxplots. The lithology of the research area consists of six lithological units: sandstone, first-phase dacite, diorite, quartz diorite, second-phase dacite, and phreatomagmatic breccia. There are five alteration zones, the overprint zone (alunite-chlorite-mica-smectite±pyrophyllite±biotite±k-feldspar), the advanced argillic zone (pyrophyllite-mica-dickite-diaspore), the argillic zone (kaolinite-mica±illite±diaspore), the phyllic zone (sericite/mica-smectite±chlorite±calcite), and the propylitic zone (chlorite-mica-smectite±epidote±calcite). The observed mineralization includes pyrite, chalcocite, enargite, and chalcopyrite, occurring in disseminated, massive, and vein forms, present at depths <150 m with Au grades ranging from 0.1 ppm to >1 ppm and Cu grades from <0.1% to 0.5%. The presence of pyrite, chalcopyrite, bornite, and covellite in stockwork is found at depths >150 m with Au grades ranging from 0.5 ppm to >1 ppm and Cu grades from 0.3% to >1%. The Cu-Au grade distribution zone is controlled by quartz diorite intrusions and is associated with argillic and phyllic alteration types. The related mineralization includes bornite-chalcopyrite-pyrite and enargite-chalcocite-pyrite assemblages, with pyrite showing a weak association. The ore deposit type is a porphyry Cu-Au system overprinted by high-sulfidation epithermal mineralization.